THIRD MOLAR ERUPTION AND EDENTULOUS SPACES-DECISIVE VARIABLES OF PROSTHODONTIC MANAGEMENT - Roxana Ionela Vasluianu; Elena-Raluca Baciu; Costin Lupu; Alice Murariu; Dana Gabriela Budală (Romanian Society of Oral Rehabilitation, 2023)
The most serious issue confronting young institutionalized individuals is aggression towards them, as well as a loss of self-esteem as a result of a lack of respect for others. The eruption of the third molar is a major problem in young patients who need oral rehabilitation. The complexity of the clinical cases from the point of view of the necessary dental, endodontic, periodontal and surgical treatments requires the realization of provisional removable partial denture to restore the functions of the oral cavity until the completion of the jaw growth and dental eruptions. The oral rehabilitation by fixed and removable dentures, associated with the eruption stage of the third molar, requires special attention in terms of establishing the prosthetic treatment, choosing materials so as to ensure resistance, a good stability and maintenance on the prosthetic field as well as the possibility of cutting in the distal area to ensure a space for the eruption of the molar.